Effects of caffeine and carbohydrate mouth-rinses on running performance - Kor, Kenneth Kiat Kang (2017)
Endurance sports, especially running, are increasing in popularity amongst every one of all levels, but gastrointestinal problems is one of the factors limiting exercise performance. The aim of this study is to investigate the effects of caffeine and carbohydrate mouth rinsing on a 10 km self-paced running performance. It was hypothesized that both caffeine and carbohydrate mouth rinsing would produce similar results, with no difference in time to completion. Ten recreationally active males (Mean (SD): 25.9 (2.6) years) completed two experimental trials following an overnight fast. A randomized, double-blinded, cross-over design was employed whereby participants completed a 10 km running time-trial in the fastest time possible on a treadmill. Participants mouth-rinsed for 30s before the commencement of the time-trial and a further nine times throughout the time-trial. All mouth-rinses were 25 ml and contained either 1.2% CAF or 6.4% CHO. Time to completion, heart rate (HR) and rate of perceived exertion (RPE) were recorded throughout. Time to completion was analysed using a paired sample t-test whereas HR and RPE were analysed using a Wilcoxon test, with an alpha of 0.05. No significant difference (p = 0.125) was found between time to completion between the CAF (Mean [95% CI]: 63.32 [58.32, 68.32] mins) and CHO (65.27 [60.95, 69.59] mins) trials, so were HR (p = 0.799) and RPE (p = 0.890). The results showed that mouth rinsing with CAF or CHO in the buccal cavity does not significantly enhance running performance nor lower the rate of perceived exertion.